Ionic Silver Nanoparticles (Ag+) Sebagai Bahan Antibiotik Alternatif Untuk Salmonella Typhymurium - Palupi, Saraswati Kendis Intan; Suparno, Suparno (Department of Physics, Sebelas Maret University, 2020)
This study aims to determine the ability of ionic silver nanoparticles (ISN) Ag+ as an antibiotic material to inhibit the growth of Salmonella typhimurium. ISN are produced by electrolysis using two AgBr bars as electrodes with distilled water as electrolyte solvents. The effect of electrolysis time on ISN concentration and electrical conductivity was observed with a TDS and EC meter. All ISN samples have been characterized by UV-Vis spectrophotometer, AAS, and PSA. The results showed the concentration of ISN and the electrical conductivity of the solution increased with the length of time of electrolysis. UV-Vis spectrophotometer test results have shown the peak of absorbance at a wavelength of 416.5-417 nm. The concentration test using AAS has shown that the concentration of ISN for TDS 11 ppm, 20 ppm and 29 ppm is 9.8 ppm, 17.6 ppm, and 23.9 ppm respectively. While the size of silver nanoparticles PSA test results have shown (76.8 ± 0.667) nm. The results of the test of the ability of ISN as an antibiotic Salmonella typhimurium showed the formation of a clear zone until the 72th hour with the largest average diameter in the stationary phase area (hours 24-72) was 7.39 ± 0.04 mm for a concentration of 20 ppm.